Pengaruh Influencer Review Dan Trend Terhadap Purchasing Kosmetik Online Shop Pada Gen Z Di Aceh Barat - Cut Chairunnisa (Indonesia Economic Journal, 2026)
This study aims to analyze the influence of Influencer Reviews and Trends on the purchasing of cosmetic products in online shops among social media users, particularly students of Teuku Umar University. The background of this research is the increasing phenomenon of online cosmetic purchases driven by the widespread presence of influencer review content and viral trends on platforms such as TikTok, Instagram, and YouTube. The research method used is quantitative with a survey approach. The sample consisted of 100 respondents selected using purposive sampling with the criteria of having seen influencer reviews and having purchased cosmetic products through a marketplace. Data analysis included descriptive analysis, validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-test, and F-test with the assistance of the Statistical Package for the Social Sciences (SPSS) version 25. The results of the t-test (partial) show that Influencer Review (X1) has a positive and significant effect on Purchasing, indicating that the credibility, attractiveness, and expertise of influencers can increase interest and purchasing decisions for cosmetic products online. The Trend variable (X2) also has a positive and significant effect on Purchasing, suggesting that viral content, challenges, popular hashtags, and social media exposure can trigger purchases. Furthermore, the results of the F-test (simultaneous) indicate that both independent variables have a significant combined effect on Purchasing with a significance value < 0.05. The Adjusted R² value of 0.349 indicates that 34.9% of the variation in Purchasing can be explained by Influencer Reviews and Trends, while the remaining 65.1% is influenced by other factors outside this study. This research concludes that Influencer Reviews and Trends are dominant factors in shaping online cosmetic purchasing decisions. Therefore, business actors are advised to collaborate with credible influencers and leverage viral trends to enhance consumer attention, trust, and purchase intention on digital platforms.